Pengaruh Berkembangnya Pasar Modal di Indonesia - Aisha Alvia; Habilla Anshari; Maryam Batubara (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The capital market in Indonesia is developing rapidly. The existence of the capital market means that people who are located or have more financial can invest funds by getting a profit, besides that the company can use the funds for investment purposes without having to wait for the availability of funds from the company's activities.The capital market is one of the financial sectors that is developing very rapidly. An indicator that is often used to see the development of the Indonesian capital market is the composite stock price index (JCI). Which is one of the stock market indices used by the Indonesia Stock Exchange (IDX). JCI is an indicator of stock price movements contained in the IDX as a whole. The problem in this study is what are the factors that influence the development of the capital market in Indonesia